Penerapan Pembalikan Beban Pembuktian (Omkering van Bewijslast) Pada Peradilan Tindak Pidana Korupsi dalam Perspektif Hak Asasi Manusia Terdakwa - Zainal Muhtar (Supremasi Hukum: Jurnal Kajian Ilmu Hukum, 2013)
Corruption was considered detrimental to social and economic rights of Indonesian society that is an extra-ordinary crime and a common enemy Indonesian society and the nation as a whole. Therefore, necessary extra-ordinary enforcement and extra-ordinary measures anyway. One such action is to conduct a comprehensive shift to the existing verification system , by applying the reversal of burden of proof (omkering van bewijslast) in UU PTPK. The application of this principle tends to cause the shift of the presumption of innocence to the presumption of guilt, whereas protection and respect for Human Rights defendant can not be reduced at all and for any reason (non- derogable right). This paper attempts to examine the application of the reversal of the burden of proof (omkering van bewijslast) in the theoretical study and practice, to find a theoretical justification for the application of the reversal of the burden of proof in relation to human rights perspective defendant.